德国潘道夫刨花干燥机传动系统的改造 - 谭红江 (Jixie chuandong)
The defect and failure cause of Germany Ponndorf particle drier transmission system is analyzed.The transformation method of Germany Ponndorf particle drier transmission system and the transformation effect is expounded.The technical support for maintenance and transformation of particle drier is provided by this study.